Revisiting the Impact of Board Gender Diversity on ESG Disclosure in the US - Muhammad Ali; Egi Arvian Firmansyah (Universitas Pasundan, 2023)
The objective of this study is to examine the effect of board gender diversity on the disclosures of environmental, social, and governance (ESG) of Fortune 500 non- financial firms in the United States of America. This study utilized a sample of US non-financial firms between 2013-2022 and generated unbalanced panel data for 343 non-financial firms from the Bloomberg database comprising 2,145 firm-year observations. The results indicate that board gender diversity is positively associated with ESG disclosure. Besides, the board gender diversity also has a significant positive relationship with individual components of ESG disclosure: environmental, social, and governance disclosures. This study also explores the impact of a critical mass of women on boards on the ESG disclosure score and its three components individually. In addition, the findings suggest that the critical mass of female board members favorably impacts the environmental and governance components of the ESG score. However, their contribution to the social score is limited. This study contributes to the limited but expanding literature on the relationship between corporate governance and ESG disclosure and encourages firms in developing nations to appoint more women to the boards.